Upaya Meningkatkan Kebersihan Area Bar di Food And Beverage Service Department Holiday Inn Resort Baruna Bali - Udayana, Kadek Dwiky Indra; Widiastini, Ni Made Ary (Universitas Pendidikan Ganesha, 2020)
This study aims to (1) To determine the application of cleanliness is important to do at the bar outlets at the Holiday Inn Resort Baruna Bali, (2) Efforts are made to maintain the cleanliness of the bars at the Holiday Inn Resort Baruna Bali in order to produce quality drinks. The subjects of this study were Supervisors and seniors at the Holiday Inn Resort Baruna Bali bar. The object of research is the standard application of cleanliness in Bar Holiday Inn Resort Baruna Bali. Data were collected using descriptive qualitative analysis and observation. The results showed that the lack of application of cleanliness in handling. Therefore there needs to be an increase in cleanliness at the Bar Holiday Inn Resort Baruna Bali